Contemporary Women’s Ghost Stories - Wisker, Gina. author. aut Link
XII, 274 p.
Keywords: “In this compelling exploration of the gendered resonances of ghosts, revenants and superstitions for the contemporary woman writer, Gina Wisker asks us to look again at the dark secrets which leak out of haunted spaces. Revelatory in the connections it makes between female-authored Gothic narratives and forgotten crimes, violence, injustices and oppression, it advances arguments about the ghost story’s inventiveness by critiquing the terrifying silences of history and the trauma of place.” — Dr Emma Liggins, Reader in English Literature, Manchester Metropolitan University, UK This book offers new insights on socially and culturally engaged Gothic ghost stories by twentieth century and contemporary female writers; including Shirley Jackson, Angela Carter, Toni Morrison, Ali Smith, Susan Hill, Catherine Lim, Kate Mosse, Daphne du Maurier, Helen Dunmore, Michele Roberts, and Zheng Cho. Through the ghostly body, possessions and visitations, women’s ghost stories exposelinks between the political and personal, genocides and domestic tyrannies, providing unceasing reminders of violence and violations. Women, like ghosts, have historically lurked in the background, incarcerated in domestic spaces and roles by familial and hereditary norms. They have been disenfranchised legally and politically, sold on dreams of romance and domesticity. Like unquiet spirits that cannot be silenced, women’s ghost stories speak the unspeakable, revealing these contradictions and oppressions. Wisker’s book demonstrates that in terms of women’s ghost stories, there is much to point the spectral finger at and much to speak out about. Gina Wisker is an Associate Professor at the University of Bath, and Professor Emeritus of Higher Education & Contemporary Literature at the University of Brighton, UK. Gina has published twenty-six books and over one hundred and forty articles, including Key Concepts in Postcolonial Literature (2007); Horror Fiction:An Introduction (2005); Margaret Atwood, an Introduction to Critical Views of Her Fiction (2012) and Contemporary Women’s Gothic Fiction (2016). Gina co-edits the online dark fantasy journal Dissections (2006–), Spokes poetry magazine (1990s–) and hosts ‘words and worlds’ readings for ICFA. Gina lives in Cambridge, has two sons and a feisty poodle.